The Ethics of International Trade: Use of Deviation from Average World Price to Indicate Possible Wrongdoing - Paul, Karen (Business ethics quarterly, 1994)
The measure proposed here, the ratio of the price reported in a given trade to the average world price for that commodity, is based on the average world price for a given commodity reported for all trades between the U.S. and all other countries for a given period. This new measure can be used to enable government agencies to identify trades between U.S. firms or individuals and their counterparts in other countries which are designed to further prohibited activities such as money laundering or tax avoidance. This measure would also enable the U.S. government to monitor trade flows more accurately, facilitating more analysis of trade imbalances between countries and tracking trade in strategic materials, for example, weapons. Use of this new measure could enable naive buyers and sellers of goods, for example, those situated in remote or underdeveloped markets, to know what their counterparts in more central and informed countries are paying or being paid for comparable goods, and hence to become more informed as trading partners.